Production of Paracheirodon innesi on Different Densities in Recirculating System - Budiardi, T.; Gemawaty, N.; Wahjuningrum, D. (Jurnal Akuakultur Indonesia, 2007)
The objective of this research was to know production of neon tetra Paracheirodon innesi reared in recirculating system with density 20, 40 and 60 litre-1. Fish with 1.80 ± 0.04 cm lenghts were cultured in 30 x 20 x 20 cm aquarium in recirculating system, during 28 days. Result of this research showed that density of fish rearing affected  survival rate (p0.05) was observed on body lenght, growth of body lenght and coefficient of varians. Keywords: Density, production, growth, survival rate dan Paracheirodon innesi   ABSTRAK Penelitian ini bertujuan untuk mengetahui produksi ikan neon tetra Paracheirodon innesi ukuran L yang dipelihara pada sistem resirkulasi dengan kepadatan 20, 40 dan 60 ekor/L. Benih ikan neon tetra yang digunakan berukuran sedang (medium) dengan panjang awal 1,80 ± 0,04 cm. Ikan ini dipelihara pada akuarium dengan ukuran 30cm x 20cm x 20cm selama 28 hari. Hasil penelitian ini menunjukkan bahwa kepadatan pemeliharaan memberikan pengaruh terhadap kelangsungan hidup (p0,05). Kata kunci : Padat penebaran, produksi, pertumbuhan, kelangsungan hidup, neon tetra dan Paracheirodon innesi